2016
DOI: 10.1021/jacs.6b04432
|View full text |Cite
|
Sign up to set email alerts
|

Functional Modulation of a G Protein-Coupled Receptor Conformational Landscape in a Lipid Bilayer

Abstract: Mapping the conformational landscape of G protein-coupled receptors (GPCRs), and in particular how this landscape is modulated by the membrane environment, is required to gain a clear picture of how signaling proceeds. To this end, we have developed an original strategy based on solution-state nuclear magnetic resonance combined with an efficient isotope labeling scheme. This strategy was applied to a typical GPCR, the leukotriene B4 receptor BLT2, reconstituted in a lipid bilayer. Because of this, we are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 36 publications
(72 reference statements)
10
92
0
Order By: Relevance
“…Achieving conformational homogeneity is the key to crystallize membrane proteins (Loll, 2014). In agreement with our results, a recent experimental study showed that CHS impacts the conformational dynamics of a GPCR leading to a restricted conformational space (Casiraghi et al, 2016). Earlier it was experimentally reported that cholesterol induces a more compact conformational state of the oxytocin receptor (Muth et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Achieving conformational homogeneity is the key to crystallize membrane proteins (Loll, 2014). In agreement with our results, a recent experimental study showed that CHS impacts the conformational dynamics of a GPCR leading to a restricted conformational space (Casiraghi et al, 2016). Earlier it was experimentally reported that cholesterol induces a more compact conformational state of the oxytocin receptor (Muth et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The literature reporting on the specific functional role of cholesterol and other lipids is extensive (Pucadyil and Chattopadhyay, 2006; Gimpl, 2016). It has been experimentally shown that cholesterol affects the conformation (Muth et al, 2011; Casiraghi et al, 2016) and function (Gimpl et al, 1997; Paila et al, 2011; Pucadyil and Chattopadhyay, 2006; Casiraghi et al, 2016; Jafurulla et al, 2014) of many GPCRs. Based on X-ray crystal structures cholesterol has specific contacts with β 2 AR (Cherezov et al, 2007; Hanson et al, 2008), suggesting that β 2 AR has binding sites for cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to biophysical investigation of the GHS receptor, a detailed pharmacological characterization was carried out using homogenous fluorescence assays as described in the literature29. Figure 1A shows the dose-dependent atto520-ghrelin ligand binding plots of the GHS receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Functionality of GHS receptor preparations was tested by a homogeneous fluorescence binding assay using [Dpr 3 -Oct; Dpr 16 -atto520]-ghrelin (ghrelin-atto520), detecting fluorescence enhancement upon receptor binding29. Functionality of the fluorescent tracer ghrelin-atto520 was verified in 3 H-inositol phosphate accumulation assays as described before displaying an EC 50 value of 1.7 nM (pEC 50  = 8.8 ± 0.10; ghrelin: pEC 50  = 9.0 ± 0.15).…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of the binding affinity of the Y 1 R was carried out using homogenous fluorescence assays as described in the literature 47 . The reconstituted receptor was incubated in increasing concentrations with 50 nM fluorescently labelled NPY (NPY-atto520) overnight at room temperature in 50 mM NaP, pH 7.0 and 0.1% BSA.…”
Section: Methodsmentioning
confidence: 99%